1994
DOI: 10.1104/pp.104.2.657
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Stress-Induced Proteoid Roots Show Altered Metabolism in Lupinus albus

Abstract: Proteoid roots develop in Lupinus albus 1. in response to nutrient stress, especially P. Proteoid roots excrete citrate and thus increase the availability of P, Fe, and Mn in the rhizosphere. In an effort to understand citrate synthesis and organic acid metabolism in proteoid roots of lupin, we have evaluated i n vitro enzyme activities of citrate synthase (CS), malate dehydrogenase (MDH), and phosphoenolpyruvate carboxylase (PEPC) i n proteoid and normal roots of plants grown with or without P. Organic acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
162
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(177 citation statements)
references
References 33 publications
12
162
2
1
Order By: Relevance
“…Some species (e.g., white lupin, L. albus) are less sensitive to the presence of P in the soil and will produce some cluster roots even at P levels found in fertile agricultural soils (Keerthisinghe et al, 1998). When the ability of other nutrient stresses to stimulate cluster root formation in white lupin was tested, it was found that a -Mn treatment had a small stimulatory effect, while -N, -K and -Fe had none (Johnson et al, 1994).…”
Section: Cluster Rootsmentioning
confidence: 99%
“…Some species (e.g., white lupin, L. albus) are less sensitive to the presence of P in the soil and will produce some cluster roots even at P levels found in fertile agricultural soils (Keerthisinghe et al, 1998). When the ability of other nutrient stresses to stimulate cluster root formation in white lupin was tested, it was found that a -Mn treatment had a small stimulatory effect, while -N, -K and -Fe had none (Johnson et al, 1994).…”
Section: Cluster Rootsmentioning
confidence: 99%
“…[24,40] Iron-and P-deficiency induce accumulation of organic acids (i.e. citric acid), [41] which may play an important role in Cr translocation. However, while Cr(III) Non-AM sunflower plants had marginal P concentrations, there was no difference in tissue Cr concentration and total Cr accumulation (roots, leaves, total plant) was less than in AM plants.…”
Section: Davies Et Almentioning
confidence: 99%
“…citrate, malate; Johnson et al, 1996aJohnson et al, , 1996bWatt and Evans, 1999a;Ryan et al, 2001). The role of PEPC is to replenish TCA intermediates by catalyzing the carboxylation of phosphoenolpyruvate to form oxaloacetate (Johnson et al, 1994). Johnson et al (1994) found that PEPC-mediated nonphotosynthetic CO 2 fixation provided a quarter of the carbon exuded as citrate from cluster roots of L. albus.…”
mentioning
confidence: 99%
“…The evidence to support metabolic specialization comes predominately from studies with L. albus (Johnson et al, 1994(Johnson et al, , 1996a(Johnson et al, , 1996bKeerthisinghe et al, 1998;Neumann and Rö mheld, 1999;Neumann et al, 1999;Evans, 1999a, 1999b), and is based on three sets of observations: (1) genes involved in citrate synthesis are up-regulated when citrate exudation occurs from cluster roots (e.g. phosphoenolpyruvate carboxylase [PEPC]; Neumann et al, 1999;Kania et al, 2003;Uhde-Stone et al, 2003); (2) genes involved in citrate catabolism are down-regulated when citrate exudation occurs from cluster roots (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation